Is fertility related to religiosity? Evidence from Spain - Pablo Bra\~nas-Garza; Shoshana Neuman (Institute for the Study of Labor (IZA), 2006)
The paper explores the relationship between religiosity and fertility among Catholics in Spain, thereby answering the question whether the two parallel trends of dramatic drops in fertility and in religiosity are inter-related. It looks at current religiosity as well as exposure to religiosity during childhood. A unique, rich, data set is employed. It includes various dimensions of religiosity: respondent's religious affiliation; if he is Catholic- his current mass attendance (six levels) and his current prayer habits (eleven levels); spouse's religious affiliation; parental (maternal and paternal) and respondent's mass attendance when the respondent was a child (nine levels); Catholic education during childhood (yes/no). The multi-facet data on religiosity (rather than a single dichotomous variable) facilitates a sophisticated analysis with rigorous conclusions. The sample is restricted to married Catholic (female and male) respondents who were raised by Catholic parents, and are married to a Catholic spouse, in order to have a homogenous sample and to focus on the effect of the level (intensity) of religiosity (rather than religious affiliation) on fertility. Fertility is related to the various dimensions of religiosity- first using cross-tabulation and then using OLS regression. We find that fertility is not related to current intensity of religiosity. Exposure to religious activities during childhood has a significant effect on fertility of women (but not men): interestingly a father who was actively attending mass services has a positive effect on his daughter's future fertility (increasing the number of kids by about 0.8) while the mother's active mass participation has a reverse negative effect (leading to a decrease of one kid). Own participation in mass services during childhood has a positive effect on fertility- leading to an increase of 0.6 kids if the girl attended mass services intensively This study indicates the significance of childhood experience in shaping the 'taste for children'. It also suggests that there is no direct link between the fast secularization in Spain and the decline in birth rates.
Keywords: Z12; J12; J13; D13; 330; fertility; religion; Catholic; church attendance; prayer; parental religiosity; taste for children; Spain